Impact of the environmental protection tax on household welfare in Vietnam - Nguyen Quynh Hoa; Ngo Quoc Dung; Pham Ngoc Toan; Nguyen Thi Thu Lien (Cogent Economics & Finance, 2023)
In 2010, Vietnam promulgated the Law on Environmental Protection Tax, introducing a comprehensive package of environmental levies. However, few studies have examined the impacts of such an environmental tax within the country. This study aims to explore the effects of the environmental protection tax, leading to higher fuel prices, on household welfare in Vietnam. Using data from the 2020 Household Living Standard Survey and an input-output approach, this paper finds that the total impact is relatively modest. Interestingly, the results reveal a non-linear relationship between the total effects of rising fuel prices and per capita expenditure. Households in the top quintile are the most affected, followed by those in the third and bottom quintiles. Geographically, wealthier urban households and poorer rural households are primarily affected. These findings suggest that increasing the environmental protection tax on petroleum products could be an effective measure to nudge households' and producers' demands toward a greener economy. Simultaneously, mitigating any adverse impacts on household welfare is crucial, particularly for poor households in rural areas. Possible solutions include (i) direct and indirect financial subsidies; (ii) clear public communication about the rationale behind an environmental tax on petroleum; (iii) promoting efficient fuel use and launching campaigns to adjust households' and producers' demand for fuel products, encouraging a shift from fossil fuels to greener energy alternatives.
Keywords: 330; environmental protection tax; household welfare; input-output analysis; petroleum; Vietnam